565 A novel long-acting interleukin-7 agonist, NT-I7, increases cytotoxic CD8+ T cells and enhances survival in mouse glioma models. (10th December 2020) - Ghosh, Subhajit; Yan, Ran; Thotala, Sukrutha; Jash, Arijita; Mahadevan, Anita; Hu, Tong; Lee, Byung; Yang, Se Hwan; Hallahan, Dennis; Chheda, Milan; Thotala, Dinesh; Campian, Jian
Abstract : Background: Radiation (RT) and temozolomide (TMZ), which are standard of care for patients with glioblastoma (GBM), can cause prolonged severe lymphopenia. Lymphopenia, in turn, is an independent risk factor for shorter survival. Interleukin-7 (IL-7) is a cytokine that is required for T cell homeostasis and proliferation. IL-7 levels are inappropriately low in GBM patients with lymphopenia. NT-I7 (efineptakin alfa) is a long-acting recombinant human IL-7 that supports the proliferation and survival CD4+ and CD8+ cells in both human and mice. We tested whether NT-I7 rescues treatment-induced lymphopenia and improves survival. Methods: Immunocompetent C57BL/6 mice bearing two intracranial glioma models (GL261 and CT2A) were treated with RT (1.8 Gy/day x 5 days), TMZ (33 mg/kg/day x 5 days) and/or NT-I7 (10 mg/kg on the final day of RT completion). We profiled the CD3, CD8, CD4, FOXP3 cells in peripheral blood over time. We also immunoprofiled cervical lymph nodes, bone marrow, thymus, spleen, and the tumor 6 days after NT-I7 treatment. Survival was monitored daily. Results: Median survival in mice treated with NT-I7 combined with RT was significantly longer than RT alone (GL261: 40d vs 34d, p<0.0021; CT2A: 90d vs 40d, p<0.0499) or NT-I7 alone (GL261: 40d vs 24d, p<0.008; CT2A: 90d vs 32d, p<0.0154). NT-I7 with RT was just as effective as NT-I7 combined with RT and TMZ in both GL261(40d vs 47d) and CT2A (90d vs 90d). Cytotoxic CD8+ T cells were increased in both peripheral blood (0.66 x 105 to 3.34 x 105; P≤0.0001) and tumor (0.53 x 103 to 1.83 x 103; P≤0.0001) in mice treated with NT-I7 when compared to control. Similarly, NT-I7 in combination with RT increased the CD8+ T cells in peripheral blood (0.658 x 105 to 1.839 x 105 P≤0.0001) when compared to RT alone. There were decreases in tumor infiltrating FOXP3+ T-reg cells in mice treated with NT-I7 (1.9 x 104 to 0.75 x 104 P≤0.0001) and NT-I7 + RT (1.9 x 104 to 0.59 x 104 P≤0.0001) when compared to the control group without NT-I7. In addition, NT- I7 treatment increased CD8+ T cells in thymus, spleen, and lymph nodes. Conclusions: NT-I7 enhances cytotoxic CD8+ T lymphocytes systemically and in the tumor microenvironment, and improves survival. A phase I/II trial to evaluate NT-I7 in patients with high-grade gliomas is ongoing (NCT03687957 ).